Visual outcomes, binocular vision and subjective accommodation after Crystalens HD accommodating intraocular lens implantation - Rajska, Kinga; Loba, Piotr; Wilczynski, Michal; Broniarczyk-Loba, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Objective : To evaluate visual acuity, binocular vision and subjective accommodation in patients after Crystalens HD accommodating intraocular lenses (IOLs) or monofocal IOLs implantation. Material and methods : 75 consecutive patients (aged 48 to 75 years) after bilateral cataract surgery with acrylic monofocal IOL (n = 36) or single-optic accommodating IOL (Crystalens HD) (n = 19) implantation and healthy presbyopic population (n = 20) were enrolled. Presence of asthenopic symptoms, diplopia and spectacle dependence was assessed. Orthoptic status, prism bar and amblyoscopic motor fusion, Frisby Near Stereotest, TNO and Titmus tests were performed. Convergence and subjective accommodation were evaluated using Krimsky-Prince rule. Results : Asthenopic symptoms were present respectively in 36.1%, 15.8% and 35.0% of patients and spectacle dependency was reported by 86.1%, 21.1% and 85.0% of patients in subsequent groups. Negative fusional distance vergence means were 9.53 ± 5.53, 8.05 ± 3.66, 6.65 ± 5.33 respectively (p = .039). Negative fusional near vergence means were 26.53 ± 11.39, 28.68 ± 11.70, 20.75 ± 12.60 in subsequent groups (p = .001). Mean subjective right eye/ left eye accommodation was 5.01 ± 1.47/ 4.86 ± 1.72, 6.29 ± 2.33/ 6.02 ± 1.90, 4.13 ± 0.89/ 4.22 ± 1.3 respectively (p = .009). There were no statistically significant differences between groups in positive fusional vergence, stereoacuity and near point of convergence. Conclusions : Bilateral accommodating IOL implantation provided full binocular vision in the majority of patients. Spectacle dependence and asthenopic symptoms were less frequent in patients with accommodating IOLs. Accommodating IOLs provided significantly better useful accommodation than monofocal IOLs.